2013
DOI: 10.3168/jds.2013-6713
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority trial comparing a first-generation cephalosporin with a third-generation cephalosporin in the treatment of nonsevere clinical mastitis in dairy cows

Abstract: The objective of this study was to evaluate the noninferiority of 2 intramammary treatments for nonsevere clinical mastitis. The 2 treatments were a first-generation cephalosporin (cephapirin sodium, 2 treatments 12h apart) and a third-generation cephalosporin (ceftiofur hydrochloride, treatments once a day for 5d). A total of 296 cases on 7 farms met the enrollment criteria for the study. Streptococcus dysgalactiae was the most common bacterial species identified in milk samples from cows with mild to moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(86 citation statements)
references
References 29 publications
6
73
6
1
Order By: Relevance
“…S1). S. uberis, the major causative agent of bovine mastitis (Schukken et al, 2013), was found to be the most prevalent member of the genus Streptococcus and, interestingly, more than half of the Bacillus spp. isolates belonged to the species B. pumilus and 23% to B. licheniformis.…”
Section: Discussionmentioning
confidence: 99%
“…S1). S. uberis, the major causative agent of bovine mastitis (Schukken et al, 2013), was found to be the most prevalent member of the genus Streptococcus and, interestingly, more than half of the Bacillus spp. isolates belonged to the species B. pumilus and 23% to B. licheniformis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained during a clinical trial in New York conducted in 2010 and 2011, which enrolled 296 cases of mastitis from 7 farms milking 357 to 1578 cows. 11 In that study, the most commonly isolated pathogen was Streptococcus dysgalactiae, followed by Escherichia coli, other esculin-positive cocci, Streptococcus uberis, and Klebsiella species.…”
Section: Etiologymentioning
confidence: 97%
“…36 The drug was evaluated at 2 dose levels; data for the approved tube dose of 125 mg cephapirin are reported here. Ceftiofur was also a treatment in the 2013 study 11 described in the section about cephapirin and in an earlier study that focused on Gram-negative pathogens:…”
Section: Treatment Of Mastitis In Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…. Although current guidelines do not recommend the use of intramammary antibiotics for cows diagnosed with Gram-negative mastitis314, improved bacteriological and clinical outcomes have been shown in mastitic cows treated with third-generation cephalosporins compared with other antimicrobials or untreated controls1516. However, the impact of these broad-spectrum antibiotics on the milk microbiota (other than major pathogens) remains unknown.…”
mentioning
confidence: 99%